Prevalence of oral health status in visually impaired children - KVKK Reddy; A Sharma (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2011)
Introduction: The epidemiological investigation was carried out among 228 children selected from two schools of similar socioeconomic strata in and around Chennai city. Materials and Methods: The study population consisted of 128 visually impaired and 100 normal school going children in the age group of 6-15 years. The examination procedure and criteria were those recommended by W.H.O. in 1997. Results: The mean DMFT/deft was 1.1 and 0.17,0.87 and 0.47 in visually impaired and normal children, respectively. Oral hygiene levels in both groups were: mean value in good category was 0.19 and 0.67, in fair category was 0.22 and 0.1, and in poor category 0.40 and 0.23 in visually impaired children and normal children, respectively. Trauma experienced children were 0.29 and 0.13 in visually impaired children and normal children, respectively. Conclusion: The conclusions drawn from this study were that there was a greater prevalence of dental caries, poorer oral hygiene, and higher incidence of trauma in visually impaired children.